2018
DOI: 10.1080/00131911.2018.1487387
|View full text |Cite
|
Sign up to set email alerts
|

Are school boards and educational quality related? Results of an international literature review

Abstract: School boards have a central position in educational governance. They have to guarantee quality, monitor results and intervene if needed. In this article we report the results of a systematic literature review meant to identify what school boards do to contribute to educational quality. After five steps of literature selection and refinement, our initial database of 4939 was reduced to 16 empirical articles. This shows that there is actually very little empirical research on the relation between boards and edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…Surprisingly the chairs place parents in third place even though existing research evidence argues that family background is hugely important for school performance (Hattie, 2009). Honingh et al (2020) argue that schoolboards set prerequisites for the schools' work policies and Hooge and Honingh (2014) note that the board's governance is a precondition for those who are directly responsible for the teaching. Honingh et al (2020) further state that the relationship between schoolboards and the superintendent is essential to educational quality.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Surprisingly the chairs place parents in third place even though existing research evidence argues that family background is hugely important for school performance (Hattie, 2009). Honingh et al (2020) argue that schoolboards set prerequisites for the schools' work policies and Hooge and Honingh (2014) note that the board's governance is a precondition for those who are directly responsible for the teaching. Honingh et al (2020) further state that the relationship between schoolboards and the superintendent is essential to educational quality.…”
Section: Discussionmentioning
confidence: 99%
“…In the final sections results of the study are reported and the main outcomes are discussed. Honingh et al (2020) note that there are differences between boards within countries as well as between countries and one cannot draw general conclusions or transfer ideas of working methods from one country to another. In Sweden, neither the role of nor the expectations of the superintendent by local schoolboards have been subject to extensive research.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations